Electrophysiological effects of N6-cyclopentyl-adenosine and [-]-N6-[phenylisopropyl]-adenosine on pacemaker cells in sinoatrial node of guinea pigs - Li Yu-Long; He Rui-Rong (Acta Pharmacologica Sinica, 2016)
The electrophysiological effects of N6-cyclopentyladenosine (CPA) and [-]-N6-[phenylisopropyl]adenosine (R-PIA) (both are selective adenosine A1 receptor agonists) on pacemaker cells in sinoatrial (SA) node of guinea pigs were investigated using intracellular microelectrodes. CPA and R-PIA increased the amplitude of action potential, amplitude of the maximal diastolic potential and maximal rate of depolarization (phase 0), but decreased the velocity of diastolic (phase 4) depolarization, the rate of pacemaker firing, and the duration of 90% repolarization in pacemaker cells of guinea pigs. 8-Phenyltheophylline (a nonselective antagonist of adenosine receptors) and glibenclamide (a potent blocker of ATP-sensitive K+ channels) inhibited the electrophysiological responses of pacemaker cells to CPA. These results suggest that the electrophysiological changes induced by CPA are adenosine receptor-dependent and mainly mediated by activation of ATP-sensitive K+ channels coupled to adenosine receptors.